Comparison of Stress In Peri-Implant Bone of Anterior Maxilla on Loading of Straight and Angulated Platform Switched Implant Abutments - A 3D Finite Element Analysis - Vijapure, Shashank; Singh, Nisha; Yadav, Vikender Singh; Kumar, Shailesh; Kiran, Kamini (Archives of Clinical and Medical Case Reports, 2020)
Background: Literature have shown the microbiological and mechanical benefits gained from using platform switching. Also there is increasing need for intentional inclination of the implants in specific situations like those placed in the anterior maxilla. There are no studies that evaluate the bone behaviour when using abutments associated with the principle of platform switching in different angulations in anterior maxilla. The aim of the present study was to measure and compare the stress distribution on peri-implant bone when implants are placed in the anterior maxilla using 2 different abutments with different angulations and 2 different load conditions, by means of 3D-Finite Element Analysis (FEA) which might be a powerful and effective tool to visualize such a situation. Materials and Methods: Six mathematical models of implant-supported central incisor were created with varying abutment angulations: straight abutment (S1 and S2), angulated abutment at 15 degrees (A1 and A2) and angulated abutment at 20 degrees (A3 & A4), submitted to 2 loading conditions (146 N): S1, A1 and A3 oblique loading (45 degrees) and S2, A2 and A4 axial loading, parallel to the long axis of the implant. Maximum (Rmax) and minimum (Rmin) principal stress values were obtained for cortical and trabecular bone. Results: All models showed higher stress on the peri-implant bone when subjected to oblique loading. For the cortical bone, the maximum principal stress (σ max) was highest in A1(45.53) followed by S1(34.82), A2(30.31), A3(24.85), S2(19.69) MPa and the least being in A4(16.57). For the trabecular bone, the σ max was highest in S1(8.75), followed by A1(12.12), S1(8.75), A2(7.12), A3(6.18), A4(4.12), and in S2(3.28) being the least. Conclusion: Implants demonstrated increased maximum principal stress in oblique loading compared to axial loading in all the models. Maxi